2019
DOI: 10.1371/journal.pone.0209986
|View full text |Cite
|
Sign up to set email alerts
|

Using a Bayesian network to understand the importance of coastal storms and undeveloped landscapes for the creation and maintenance of early successional habitat

Abstract: Coastal storms have consequences for human lives and infrastructure but also create important early successional habitats for myriad species. For example, storm-induced overwash creates nesting habitat for shorebirds like piping plovers ( Charadrius melodus ). We examined how piping plover habitat extent and location changed on barrier islands in New York, New Jersey, and Virginia after Hurricane Sandy made landfall following the 2012 breeding season. We modeled nesting habitat using a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…On Long Island, New York, Piping Plovers nested and reared broods on all 1‐km beach segments with ephemeral pools or bay tidal flats but nested in less than half of segments without those foraging habitats (Elias et al 2000). Cohen et al (2009) documented rapid Piping Plover colonization of a Long Island site after a series of storms created new nesting habitat adjacent to bay‐side intertidal flats, while others (Maslo et al 2019, Zeigler et al 2019 a ) observed rapid colonization in washovers by nesting piping plovers throughout the Mid‐Atlantic region following Hurricane Sandy in 2012. In New Jersey, Piping Plover nests were split evenly between sites with and without non‐ocean foraging habitats, but birds initiated nests in washovers if those features were present (Maslo et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On Long Island, New York, Piping Plovers nested and reared broods on all 1‐km beach segments with ephemeral pools or bay tidal flats but nested in less than half of segments without those foraging habitats (Elias et al 2000). Cohen et al (2009) documented rapid Piping Plover colonization of a Long Island site after a series of storms created new nesting habitat adjacent to bay‐side intertidal flats, while others (Maslo et al 2019, Zeigler et al 2019 a ) observed rapid colonization in washovers by nesting piping plovers throughout the Mid‐Atlantic region following Hurricane Sandy in 2012. In New Jersey, Piping Plover nests were split evenly between sites with and without non‐ocean foraging habitats, but birds initiated nests in washovers if those features were present (Maslo et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This could be a major factor explaining the 1.40 breeding pairs of piping plovers per mile of sandy ocean beach in New England in 2015, compared with 0.81 and 0.75 breeding pairs per mile, respectively, in New York–New Jersey and the Southern recovery units (Appendix : Table S3). Furthermore, variable trends in the number of breeding pairs in these two recovery units (USFWS 2019) appear to respond strongly to availability of washover and accessibility of nest sites to MOSH (Schupp et al 2013, Zeigler et al 2019 a ). Cohen et al (2009) found that peak density of Piping Plovers in the portion of their Long Island, New York study area where chicks had access to both ocean‐ and bay‐side foraging habitat was more than double the density of Piping Plovers in adjacent habitat without accessible MOSH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BNs are directed acyclic graphs which link variables by probabilities based on first-order Markov relations. The uses of BNs are many, including the analysis of the impacts of storm events on coastal environments [ 1 ], the assessment of ecosystem services and avalanche protection [ 2 ], the applications of informing decision-making under uncertainty [ 3 ], and much more. The advantages of BNs over traditional, frequentist statistical approaches are in their flexibility to handle multiple kinds of data, capacity to integrate expert-elicited knowledge, robustness to missing data, availability of machine-learning algorithms for the structuring and parameterizing of the models, and especially in their explicit representation of uncertainty and its propagation in calculations of probability outcomes [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%